2021
DOI: 10.1038/s41467-021-21618-1
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalysis-mediated drug-free sustainable cancer therapy using nanocatalyst

Abstract: Drug therapy unavoidably brings toxic side effects and drug content-limited therapeutic efficacy although many nanocarriers have been developed to improve them to a certain extent. In this work, a concept of drug-free therapeutics is proposed and defined as a therapeutic methodology without the use of traditional toxic drugs, without the consumption of therapeutic agents during treatment but with the inexhaustible therapeutic capability to maximize the benefit of treatment, and a Z-scheme SnS1.68-WO2.41 nanoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 52 publications
0
103
0
Order By: Relevance
“…encapsulated self‐replicating RNA in lipid nanoparticles (LNP) and observed anti‐tumor effect in several mouse models of cancer. [ 167 , 168 ] However, just as what Sun, et al. mentioned, there may be misunderstanding in the development of nanodrugs.…”
Section: Overview Of Cancer Therapies and Other Tumor‐related Immune Cellsmentioning
confidence: 99%
“…encapsulated self‐replicating RNA in lipid nanoparticles (LNP) and observed anti‐tumor effect in several mouse models of cancer. [ 167 , 168 ] However, just as what Sun, et al. mentioned, there may be misunderstanding in the development of nanodrugs.…”
Section: Overview Of Cancer Therapies and Other Tumor‐related Immune Cellsmentioning
confidence: 99%
“…79 Besides, an interesting Z-scheme SnS 1.68 -WO 2.41 nanoplatform was developed for antitumor therapy. 82 Under NIR light, the nanocatalyst can achieve oxidative holes and hydrogen molecules, leading to ROS enhancement and hydrogen therapy. Both the in vitro and in vivo experiments displayed that the nanocatalyst performed well in inducing apoptosis.…”
Section: Recent Strategies To Near-infrared Photodynamic Therapy (Npdt)mentioning
confidence: 99%
“…[55] Moreover, laser irradiation of nanoparticles would efficiently increase ROS generation, thus creating a cellular redox imbalance and destroying the tumor microenvironment (TME), both of which can directly and indirectly destroy cancer cells. [56,57] Furthermore, the acidic environment results in a high rate of ROS generation; [58] the reduction or oxidation of selenium contributes to cancer prevention, and Ti undergoes photocatalysis to generate ROS and kill cancer cells. And previous studies revealed that the monolayer TiSe 2 possesses an electron pocket persisting to low temperature in a non-bonding state to enable the ultra-fast transfer of electron-phonon coupling to the surface of the NS monolayer, [59,60] that is favorable for the photocatalysis for ROS generation.…”
Section: In Vitro Cellular Photocatalytic Effectsmentioning
confidence: 99%